Comparison of toxin removal outcomes in online hemodiafiltration and intra-dialytic exercise in high-flux hemodialysis: a prospective randomized open-label clinical study protocol. - Maheshwari V. (BioMed Central Ltd., 2018)
10.1186/1471-2369-13-156